Significance of reticulocyte hemoglobin content in the treatment of anemia in maintenance hemodialysis patients - XU Leng-nan; CHEN Xian-guang; LI Chuan-bao; LIU Xin; SUN Ying; MAO Yong-hui (Linchuang shenzangbing zazhi)
Objective To investigate the management of maintenance hemodialysis(MHD)anemia and the role of reticulocyte hemoglobin content(CHr)in its treatment.Methods Data of the patients,who underwent MHD from October 1,2019 to January 31,2020 at Beijing Hospital’s Blood Purification Center,were collected:demographic data,hemoglobin(Hb),serum ferritin(SF),transferrin saturation(TSAT),CHr,etc.;application of erythropoietin(EPO)and iron preparations.Results A total of 148 people were enrolled.Patients with Hb compliance with the reference range accounted for 35.14%.SF,TSAT and CHr were all within the target range.SF was significantly correlated with C-reactive protein(CRP)(r=0.175,P=0.037),while CHr was not(P=0.054).After excluding patients with elevated CRP,SF and CHr changed from non-correlation to significant correlation between them(r=0.272,P=0.004).By simply adjusting the dosage of EPO based on Hb,the rate of Hb compliance was not ideal.Patients with CHr decreased continually and the iron preparation was not adjusted;even if the dosage of EPO was increased,Hb could not meet the standard.CHr increased to the normal range,while the iron preparation dose was increased,and the Hb also reached the standard without increasing the EPO.Conclusions CHr is a more stable indicator that can reflect the recent iron reserve.Supplementing Iron preparation combined with CHr can better improve the situation of anemia.